2016
DOI: 10.1007/s00125-016-4172-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved glycaemia in high-fat-fed neprilysin-deficient mice is associated with reduced DPP-4 activity and increased active GLP-1 levels

Abstract: Aim/hypothesis Neprilysin, a widely expressed peptidase, is upregulated in metabolically altered states such as obesity and type 2 diabetes. Like dipeptidyl peptidase-4 (DPP-4), neprilysin can degrade and inactivate the insulinotropic peptide glucagon-like peptide-1 (GLP-1). Thus, we investigated whether neprilysin deficiency enhances active GLP-1 levels and improves glycaemia in a mouse model of high fat feeding. Methods Nep+/+ and Nep−/− mice were fed a 60% fat diet for 16 weeks, after which active GLP-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 27 publications
6
70
3
2
Order By: Relevance
“…28 In high-fat-fed neprilysin deficient mice, improved glycaemic status was associated with elevated active GLP-1 concentrations, reduced plasma dipeptidyl peptidase 4 (DPP-4) activity and improved beta cell function, suggesting beneficial metabolic effects of neprilysin inhibition. 29 Inhibition of the renin-angiotensin system has also improved glycaemic control, 30,31 and angiotensin II promotes insulin resistance, while angiotensin-1-receptor blockade modestly improves insulin sensitivity. 32 Nevertheless, the improvement of glucose metabolism by renin-angiotensin system inhibition alone is most likely to be modest.…”
Section: Discussionmentioning
confidence: 99%
“…28 In high-fat-fed neprilysin deficient mice, improved glycaemic status was associated with elevated active GLP-1 concentrations, reduced plasma dipeptidyl peptidase 4 (DPP-4) activity and improved beta cell function, suggesting beneficial metabolic effects of neprilysin inhibition. 29 Inhibition of the renin-angiotensin system has also improved glycaemic control, 30,31 and angiotensin II promotes insulin resistance, while angiotensin-1-receptor blockade modestly improves insulin sensitivity. 32 Nevertheless, the improvement of glucose metabolism by renin-angiotensin system inhibition alone is most likely to be modest.…”
Section: Discussionmentioning
confidence: 99%
“…Also, islets from neprilysin-deficient mice were protected against palmitate-induced insulin secretory dysfunction in vitro [24]. In vivo, we have shown that high-fat-fed neprilysin-deficient mice display improvements in insulin sensitivity, beta cell function and glucose tolerance, as well as beta cell mass expansion [12,25]. Furthermore, acute inhibition of neprilysin with subcutaneous or intravenous administration of a pharmacological inhibitor increased insulin secretion and sensitivity in a time-and/or dose-dependent manner in pigs, as well as in lean or obese insulin-resistant rats [3,[18][19][20] (Table 1).…”
Section: Evidence For a Beneficial Effect Of Neprilysin Inhibition Onmentioning
confidence: 82%
“…Potential mechanisms by which neprilysin inhibition improves glucose homeostasis Neprilysin is known to degrade multiple peptides that have glucoregulatory properties (see text box). Some studies support a glucose-lowering effect of neprilysin inhibition via increased plasma levels of these substrates, including GLP-1 [3,12,17,22], bradykinin [18,26] and natriuretic peptides, atrial natriuretic peptide (ANP) and B-type natriuretic peptide (BNP) [27].…”
Section: Evidence For a Beneficial Effect Of Neprilysin Inhibition Onmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the underlying pathophysiologic mechanisms are not yet clear and may be attributed to changes in the production and concentrations of various metabolically active peptides by neprilysin inhibition (i.e. atrial natriuretic peptide, BNP, bradykinin, glucagon like peptide) necessitated further investigation [37][38][39][40][41][42]. In the whole PARADIGH-HF trial the risk ratio for the primary outcome, in participants with diabetes, was 0.84 (95% CI 0.74-0.95), very similar to the overall treatment effect for the entire cohort (HR 0.80, 95% CI 0.73-0.87).…”
Section: Diabetes Mellitus Cardiovascular and Chronic Kidney Diseasesmentioning
confidence: 99%